2018
DOI: 10.1097/pcc.0000000000001463
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Bedside Clinical Neurologic Assessments in U.S. PICUs*

Abstract: Objective To understand how routine bedside clinical neurologic assessments are performed in U.S. PICUs. Design Electronic survey. Setting Academic PICUs throughout the United States. Subjects Faculty representatives from PICUs throughout the United States. Interventions None. Measurements and Main Results We surveyed how routine bedside neurologic assessments are reported to be performed in U.S. PICUs and the attitudes of respondents on the utility of these assessments. The survey contained question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Among 297 neurological ward nurses, perceived proficiency in performing an orientation exam, documenting mental status, and testing extremity muscle strength was high, while that of assessing accessory nerves, hypoglossal nerves, and cerebellar function was low (Kim et al, ). Kirschen et al () also supports this point, as their study indicates that the bedside nursing neurological assessment is suboptimal in pediatric intensive care units.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among 297 neurological ward nurses, perceived proficiency in performing an orientation exam, documenting mental status, and testing extremity muscle strength was high, while that of assessing accessory nerves, hypoglossal nerves, and cerebellar function was low (Kim et al, ). Kirschen et al () also supports this point, as their study indicates that the bedside nursing neurological assessment is suboptimal in pediatric intensive care units.…”
Section: Introductionmentioning
confidence: 85%
“…With the score of 3.32 on a 4 point scale (75th percentile) defined as the cut-off value for overall competency, 74.6% of nurses reported scores below that level. Some previous studies have also highlighted the suboptimal neurological assessment competency in assessing the consciousness level (Brunker & Harris, 2015), cerebellar function (Kim et al, 2016), application of the Glasgow Coma Scale (Waterhouse, 2008), pupil size interpretation (Brunker & Harris, 2015;Kerr et al, 2016), and bedside nursing neurological assessment practice (Kirschen et al, 2018). Standardized practice in the use of assessment scales is needed, because the greatest variation existed in training methods for the use of the instruments (Kirschen et al, 2019;Vink et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Current literature focusses mainly on predictability and reliability of the Glasgow Coma Scale, with data derived largely from adults with altered consciousness from acute neurologic injury 10 . A recent paediatric ICU survey showed that routine bedside neurologic assessments were conducted at nearly all institutions 15 . Although examination elements were variable, Glasgow Coma Scale and pupillary reflex were the most commonly performed elements.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous paediatric coma scales have been developed to address some these issues, although they have not been validated in the cardiac ICU population 10 14 We demonstrated substantial variability in neurologic assessment practices in academic paediatric medical–surgical ICUs throughout the United States, 15 although it remains unclear how neurologic assessment is performed in cardiac ICUs.…”
mentioning
confidence: 99%
“…It seems plausible that a “back to basics” approach might be appropriate so that assumptions can be questioned regarding these resource-intense studies. In this issue of the Journal, Kirschen and colleagues provide substantial evidence to advance this approach (8). Fundamental to all clinical studies – and good clinical practice – is a common understanding of the child’s neurologic condition.…”
mentioning
confidence: 99%